O thymos segundo o Liceu Feminino do Porto (1917-1927) - Correia, Luís Grosso (2000)
The present text is part of a research process on the organizational culture and the cons¬truction of identities in high schools. The construction of a school's identity is a continuous, multidimen¬sional, systemic and daily process, based on many factors from the hidden curriculum to the Internal Regulations, juridical and legal impositions to the organisation and the distribution of school tasks. In accor¬dance with this line of analysis, the identification of a school cannot be based on the classic approach of the pedagogic and school domains. It is, in fact, essential that we analyse the professional domain in its contex¬tual specificities, namely in relation to attitudes, representations and behaviours of teachers, who, in certain political and educational conjectures that marked the history of the school and the country, tended to attribute a certain value to the school and demanded the recognition of this value.